New Strategies to Detect Cardioembolism - Nichols, Emma Hitt (MD Conference Express, 2013)
Approximately 20% of all ischemic strokes are caused by cardiac embolism [Freeman WD et al. Neurotherapeutics 2011]. Cardioembolic strokes are disproportionately more disabling than strokes caused by nonembolic mechanisms due to occlusion of larger intracranial arteries and larger ischemic brain volume. This article discusses on advances in cardiac imaging, prolonged rhythm monitoring for detection of silent atrial fibrillation (AF), the potential use of biomarkers to improve identification of cardiogenic embolism, as well as the cost-effectiveness of screening patients for AF and selection of patients for screening for AF for secondary stroke prevention